نحو نظرية إسلامية في التجدد الحضاري : إسهامات بديع الزمان النورسي - Abdelaziz, Berghout (IIUM Press, International Islamic University Malaysia, 2006)
Towards an Islamic Theory in Cultural Renewal: Contributions of Badi'zaman Al - Nawrasi